Assessment of Social Capital in terms of Participation, Knowledge, Trust, and Social Cohesion: Zahedan Case Study - Bostani, Maryam Karimian; Shojaifar, Mohammad Reza; Riki, Javad; Shahbakhsh, Alireza; Hashemzehi, Soudabeh (Journal of History Culture and Art Research, 2017)
It is anticipated that the urban population in developing countries increases more than double from 2000 to 2030. This rapid population transformation to cities will be difficult. Therefore, the municipal administration will be involved in numerous challenges in cities. For this purpose, social capital as a bottom-up planning is one of the appropriate ways of management and dealing with these challenges. The aim of this study was to measure the social capital in four aspects of knowledge, participation, social cohesion, and trust in Zahedan. The research method of this research is descriptive-analytic in an applied type. Library studies and surveying (questionnaire) were used to collect the required data. The questions in this survey were designed based on four indicators of social capital. The statistical population of the present study is 575,116 people residing in Zahedan in 2011. One sample T- test was used for calculations. The results of the analysis show that the social capital criteria in the city of Zahedan are undesirable in all four criteria.